Models of Moderation-based Instructions in Teaching ENGLISH at Islamic Senior High Schools in Makassar - Hanafie Pelu; Murni Mahmud; Sahril Nur; Kisman Salija (Seminar Nasional LP2M UNM, 2021)
Abstract. Moderation is an important aspect in education since it can contribute to democratic education. The educational system in Indonesia needs to consider implementing the concept of moderation, especially in Islamic Schools. For this purpose, this research aims at exploring the models of moderation in Islamic Schools in Makassar. This research focuses on exploring moderation-based instruction models in teaching English at Islamic Senior High School in Makassar. The subject of the study is an English teacher and the students of one Islamic Senior High School in Makassar. This study employed an ethnographic research design. The researchers applied observation, interview, note-taking, and documentation of English teachers in exploring the implementation of moderation-based instruction in teaching English. Findings from this study show that PELA Model stands for Preparing material, Establishing and adopting the local wisdom, Learning to apply in ourselves before teaching others, and Applying moderation based instruction in English teaching. This model is only a suggested model that should be followed up by further research to examine and measure the effectiveness. This study will contribute to the professional knowledge of how to implement moderation in teaching English in Islamic Schools in Indonesia and provide insights for policy-making and improving the quality of primary-school level English language teaching in general.Keywords: Moderation; instruction; moderation-based instruction; English Language Teaching